Harmonization of Domestic Consumption Taxes in Central and Western African Countries - Doe, Lubin Kobla (Washington, D.C. : International Monetary Fund, 2006)
This paper examines the reform of the main domestic consumption taxes initiated by the CEMAC and the WAEMU aimed at reinforcing their economic integration. On the whole, compliance with the VAT is relatively weaker in the CEMAC than in the WAEMU. The opposite applies for excises. Major reforms would need to be undertaken by WAMZ countries, except Ghana and, to a lesser extent, Nigeria in order to align their tax structure with that of the WAEMU as planned for 2007.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet